Materiais cerâmicos cimentados sobre PEEK: propriedades ópticas, adesão e influência de tratamentos de superfície na resistência à fadiga - Machado, Pablo Soares (2023)
This work is formatted into 4 studies, which aim to evaluate (1) the influence of the foundation substrate (polyetheretherketone- PEEK; or zirconia- Yz) on the fatigue behavior of different bonded dental ceramics; (2) the scientific evidence regarding surface treatment methods and adhesive systems recommended for PEEK and their effects on its bond strength to resin-based materials; (3) the effect of different surface treatments for PEEK on its adhesion capacity and mechanical behavior; and (4) the masking ability of abutment materials by different restorative ceramics. In study 1, discs of 4 different restorative materials (polymer-infiltrated ceramic network - PICN; Lithium Disilicate - LD; Zirconia-reinforced Lithium Silicate - ZLS; Translucent Zirconia - Tz) were luted onto PEEK and Yz discs, followed by evaluation of the mechanical behavior in cyclic fatigue (n=15). The foundation substrate significantly influenced the mechanical behavior of the bonded set (Yz > PEEK). Furthermore, restorative materials with higher crystalline content showed superior fatigue performance for the same substrate. In study 2, a scoping review was carried out, where the effect of different surface treatments and adhesives applied to PEEK were discussed in order to optimize its adhesion to resin-based materials. The results demonstrated that both are essential to promote adhesion to PEEK, being the air abrasion with alumina particles a suitable option in terms of efficiency and safety. In a third study, the effect of different surface treatments was evaluated (cleaning only; grinding with 4219F diamond tip, 46 μm grain-size; air abrasion with alumina particles, 45 μm grain-size; and 98% sulfuric acid etching) firstly on PEEK and resin cement bond strength through a shear test (n=20). Subsequently, the effect of the same PEEK treatments on the fatigue mechanical behavior of LD discs luted onto this substrate was evaluated. Although air abrasion with alumina particles promoted higher bond strength values to the resin cement, no mechanical reinforcement was observed for the restorative set during the mechanical test. In study 4, the color difference (∆E00) generated by the combination of different restorative materials (LD in low, medium and high translucency levels; Tz; and bilayer system - Yz + porcelain) in A1 shade luted onto different abutment materials (Yz A1 – control; Yz opaque; LD A1; PEEK; titanium – Ti) was evaluated, as well as the effect of different cements (A1 and opaque). Bilayer systems showed greater masking ability for discolored substrates when compared to monolithic systems. Furthermore, increasing the thickness of the restorative material increased the masking potential of the abutment material.